PENGARUH CURRENT RATIO, NET PROFIT MARGIN, TOTAL ASSET TURNOVER DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Oktavia, Diana; Andarsari, Pipit Rosita (RISTANSI: Riset Akuntansi, 2023)
This study aimed to analyze the impact of the current ratio, net profit margin, total asset turnover, and debt to equity ratio on stock prices in food and beverage companies listed on the IDX during the 2021-2022 period. The study's population included 39 food and beverage companies listed on the IDX during the same period. A purposive sampling technique was employed to select the research sample, resulting in the inclusion of 16 companies that met the specified criteria. To test the research hypotheses, multiple regression analysis was conducted. The findings revealed that the current ratio, net profit margin, total asset turnover, and debt to equity ratio had no significant influence on stock prices.